Evaluation of effluxpumps gene expression in resistant Pseudomonas aeruginosa isolates in an Iranian referral hospital - Babak Pourakbari; Sahar Yaslianifard; Somaye Yaslianifard; Shima Mahmoudi; Sepideh Keshavarz-Valian; Setareh Mamishi (Iranian Journal of Microbiology, 2016)
Background and Objectives: Pseudomonas aeruginosa (PA) is one of the most important causes of nosocomial infections and has an intrinsic resistance to many antibiotics. Among all the resistance-nodulation-division (RND) pumps of P. aeruginosa, MexAB-OprM is the first efflux pump found to target multiple classes of antibiotics. This study was aimed to evaluate the expression level of genes expressing MexAB-OprM in clinical isolates of P. aeruginosa. Materials and Methods: In this study, 45 P. aeruginosa strains were isolated from patients admitted to Children's Medical Center Hospital, an Iranian referral hospital. Disk diffusion and Minimum Inhibitory Concentration (MIC) methods were used for determination of the patterns of resistance to antibiotics. Real-time PCR was used to investigate the expression level of genes of MexAB-OprM efflux pump. Results: Among 45 resistant PA isolates, the frequency of genes overexpression was as follows: MexA (n=25, 55.5%), MexB (n=24, 53.3%) and OprM (n=16, 35.5%). In addition, in 28 strains (62%) overexpression was observed in one of the studied three genes of MexAB-OprM efflux pump. Conclusion: In our study 28 isolates (62%) had increased expression level of efflux pumps genes, MexAB-OprM. Although the efflux pumps play important roles in increasing the resistance towards different antibiotics but the role of other agents and mechanisms in evolution of resistance should not be ignored. Since the concomitant overproduction of other Mex efflux systems might have additive effects on antibiotic resistance, the co-expressing of a multicomponent efflux pump is recommended. On the other hand, the concomitant overproduction of two Mex pumps might have additive effects on resistance to antibiotic. Therefore co-expressing of Mex efflux systems is recommended.